2017
DOI: 10.1007/s10072-017-3039-x
|View full text |Cite
|
Sign up to set email alerts
|

Tarsal tunnel syndrome: still more opinions than evidence. Status of the art

Abstract: Tarsal tunnel syndrome is an entrapment neuropathy of the posterior tibial nerve or its terminal branches within its fibro-osseous tunnel beneath the flexor retinaculum on the medial side of the ankle. The condition is frequently underdiagnosed leading to controversies regarding its epidemiology and to an intense debate in the literature. With the advent of nerve imaging techniques, the diagnostic confirmation and the etiological identification have become more accurate. However, management of this entrapment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
56
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 35 publications
1
56
0
Order By: Relevance
“…The causes include tarsal tunnel syndrome, which may be an underdiagnosed condition [1,16]. Doneddu et al [17] refer to a literature review that found that TTS was the fifth most commonly published nerve compression syndrome in the scientific literature from 1 January 2016 to 1 June 2016, with 134 articles, compared to 2450 indexed articles for carpal tunnel syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…The causes include tarsal tunnel syndrome, which may be an underdiagnosed condition [1,16]. Doneddu et al [17] refer to a literature review that found that TTS was the fifth most commonly published nerve compression syndrome in the scientific literature from 1 January 2016 to 1 June 2016, with 134 articles, compared to 2450 indexed articles for carpal tunnel syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…15 Patients may describe vague symptoms of foot pain, and paraesthesia, often described as worst at night or during prolonged standing. 7,16 Examination may reveal sensory changes over terminal branches of the posterior tibial nerve and tenderness on deep palpation, 16 atrophy of the intrinsic foot muscles and a positive Tinel's sign, which in CTS has a sensitivity and specificity of 82.2% and 88.9%, respectively. 17 The dorsiflexion-eversion test may assist in TTS diagnosis and is performed by passively maximally everting and dorsiflexing the ankle, while all of the metatarsophalangeal joints are maximally dorsiflexed.…”
Section: Discussionmentioning
confidence: 99%
“…We have not used injection with corticosteroid and local anaesthetic as a diagnostic or treatment modality for TTS in MPS, but this is described in the non-MPS population and could be considered. 7,16,24 Ultrasound has been used in the non-MPS population to identify space occupying lesions within the TTS and sensitivities of up to 74% have been reported for diagnosis of idiopathic TTS. 25,26 There is no literature regarding ultrasound for assessment of TTS in MPS and we have not used this modality for this purpose.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations